Do sobrevôo ao reconhecimento atento: a institucionalização da criação publicitária, pela perspectiva do habitus e dos capitais social, cultural e econômico - Petermann, Juliana (Universidade do Vale do Rio dos Sinos, 2011)
In this research, we have elaborated the following key question: from the scope of the advertising market (comprising advertising agencies, advertising professionals, awarded adverts and awarding events), how are the mechanisms for the institutionalisation of advert creation in Rio Grande do Sul configured through the perspective of habitus? To answer that question, we have defined our main objective to be the inquiry of the schemes of institutionalisation over the advertising market in the state of Rio Grande do Sul, conducted by both the perspective of habitus and of the capitals that it triggers: social, cultural and economic. Thus, we have mainly articulated the concept of institutionalisation (BERGER & LUCKMANN, 2008) and Bourdieu?s concepts of field, habitus and capital (1983, 1989, 2004, 2005, 2007a, 2007b e 2008). Due to the complexity of our object, we have employed cartography as our methodological basis for researching, which has allowed us to step away from our object: in a movement of overflying, we have visualised its intensities, which, more or less vibrant, have unfolded themselves into six plateaus that should be considered in the (re)construction of the subfield: plateau Higher Education Institutions; plateau unions and organisations; plateau agencies; plateau professionals, plateau adverts and plateau events. This overflight resulted in our macro vision. Nonetheless, these plateaus turned out to be more or less intense, and, thus, we have chosen to watchfully recognise those of more intensity: plateau agencies, plateau professionals, plateau adverts, and plateau awarding events as well, which constitute what we claim to be the advertising market. We have identified many mechanisms, and, likewise, many ways for habitus to act. However, we can highlight that the institutionalisation of advert creation in Rio Grande do Sul is a dynamic process, which is organised inside and by the schemes in which habitus acts. That because of the fact that such a process is boosted by the agents? modes of action. As we land on each plateau, but still in the process initiated in the overflight, they turned out to be of even more multiplicity, for, as they are pervaded by habitus, they constituted themselves in the actions of social, cultural and economic capitals. And it is those actions of such capitals that establish the power lines which constitute the subfield of advert creation.
Keywords: Criação publicitária; Institucionalização; Habitus; Capitais; Advert creation; Institutionalisation; Capitals; ACCNPQ::Ciências Sociais Aplicadas::Comunicação